1990
DOI: 10.1002/bjs.1800770937
|View full text |Cite
|
Sign up to set email alerts
|

Human Kupffer cells are cytotoxic against human colon adenocarcinoma

Abstract: 11/6/20928activity against human colon tumor cell lines. Hopefully, through an understanding of the cytotoxic mechanisms of human KC, strategies to stimulate human KC to prevent or eradicate hepatic metastases can be developed rationally.T h e aim of this investigation is to determine if (1) human KC are cytotoxic against human colon carcinoma in vitro, (2) this cytotoxic activity can be stimulated, and (3) human KC mediate cytotoxicity through the secretion of T N F . MATERIAL AND METHODSIsolation of human KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In vitro studies provided compelling evidence that activated Kupffer cells play a role in tumor surveillance in the liver and can exert cytotoxic or cytostatic effects on various tumor cells including human colon adenocarcinoma cells. 33 These tumoricidal effects could be induced by various mediators including cytokines. 34,35 In one of these studies, the tumoricidal effect of Kupffer cells on colon adenocarcinoma MCA26 cells in vitro was in fact linked to their ability to produce IL-1␣ and TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies provided compelling evidence that activated Kupffer cells play a role in tumor surveillance in the liver and can exert cytotoxic or cytostatic effects on various tumor cells including human colon adenocarcinoma cells. 33 These tumoricidal effects could be induced by various mediators including cytokines. 34,35 In one of these studies, the tumoricidal effect of Kupffer cells on colon adenocarcinoma MCA26 cells in vitro was in fact linked to their ability to produce IL-1␣ and TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Murine Kupffer cells activated by interferon-gamma, LPS, or macrophage colony-stimulating factor release TNF and IL-1, and these monokines produce cytotoxicity in vitro and in vivo against murine colorectal adenocarcinoma cells (27,28). Similarly, human Kupffer cells produce cytotoxicity in vitro against metastatic human colon adenocarcinoma cells through the release of TNF-a (29). TP-1 treatments in patients with HCC may produce tumor regression in part by activating hepatic Kupffer cells to release cytotoxic monokines.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies demonstrated that Kupffer cells and other macrophages can be activated to a tumoricidal state by administering biological response modifiers (BRMs) such as lipopolysaccharide [11][12][13]20], gamma interferon [11,12,21,22] and muramyl peptides [6,7,20,23,24] resulting in reduced tumor load and increased survival time. The close proximity of Kupffer cells to liver metastases makes them an attractive target for immunomodulatory therapy to stimulate macrophage defense [7,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…The close proximity of Kupffer cells to liver metastases makes them an attractive target for immunomodulatory therapy to stimulate macrophage defense [7,10,12]. Presently liposomes and microparticles are being tested as colloidal carriers to deliver BRMs to macrophages [7,10,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation